EL USO DEL MEME EN LAS ELECCIONES DEL 4-M: ESTUDIO DE LAS ESTRATEGIAS ARGUMENTATIVAS Y DE PROYECCIÓN DE IMAGEN DE ISABEL AYUSO COMO CANDIDATA Y ALCALDESA DE MADRID - Ruggeri, Alessia Anna Serena (Cultura Latinoamericana, 2022)
The present paper aims to delve deeper into the representation of women in public domains on 3.0 platforms. Specifically, emphasis will be placed on the multimodal discursive analysis in the pre-vote and post-election phase of Isabel Ayuso’s candidacy in the 4-M elections through the analysis of political memes. Among the strategies used by both politicians and users of social networks, the meme is characterized as the most powerful instrument when it comes to producing a message. At the same time is also a genre through which the political adversary is represented by means of communication rules that eradicate what is known as ‘pop communication’. In this context, we ask ourselves what is the representation of women in political domains in memes, what are the strategies used to represent their figure and if they undergo any change between the electoral campaign and post-electoral phases.